THE RELATIONSHIPS BETWEEN PARENTS ATTENTION, LEARNING INTEREST AND LEARNING DISCIPLINE WITH MATHEMATICS LEARNING OUTCOMES OF STUDENTS CLASS VII - Hilda Wulan Sari; Edi Prajitno (Universitas Ahmad Dahlan, 2018)
Many factors influence the mathematics learning outcomes that students get. Parent's attention, learning interest, and learning discipline are factors related to mathematics learning outcomes. This study aims to determine the presence or absence of positive and significant relationships between parent's attention, learning interest, and learning discipline with mathematics learning outcomes of students class VII at SMP Muhammadiyah 1 Godean District Sleman in even semester academic year of 2016/2017. The population in this study were all students of class VII at SMP Muhammadiyah 1 Godean District Sleman in the even semester academic year of 2016/2017, which consists of 5 classes with some 172 students. The random sampling technique used to get the class sample and collected class VII B as a sample. Data were collected by questionnaire method and test method. Test instruments used validity and reliability testing. Prerequisite test analysis using normality test, independence test, and linearity test. Analysis of data using simple linear regression analysis and multiple regression analysis and correlation. The results showed a positive and significant relationship between parent's attention, learning interest, and learning discipline with mathematics learning outcomes of students class VII at SMP Muhammadiyah 1 Godean District Sleman in even semester academic year of 2016/2017. It showed by Â or 2,95 > 2,93 with , and the multiple regression equation is , RC X1 = 29,39%, RC X2 = 46,99%, RC X3 = 23,62%, EC X1 = 6,87%, EC X2 = 10,99%, and EC X3 = 5,52%.